Using acoustic wave velocity to select fibre-managed plantation Eucalyptus nitens logs for laminated veneer lumber products. Issue 3 (3rd July 2019) - Blackburn, David; Vega, Mario; Nolan, Gregory
Abstract : The aims and objectives of this study were to investigate the potential to predict laminated veneer lumber (LVL) stiffness from wood properties measured on trees and logs, and determine variation in log, wood and veneer properties as a function of tree height and age. Log selections were made from trees in three stands that were planned for harvesting at 14, 20 and 21 years of age. Rotary peeled veneer recovery from the logs was on average 65%. After drying, Metriguard testing showed over 50% of the veneer had an estimated dynamic modulus of elasticity (MOEdyn ) above 12 GPa, with 20% above 14 GPa, and that veneer from the second log by tree height had higher MOEdyn values. In visual assessment to the AS/NZS 2269.0:2012 Standard, no veneer could be utilised in a panels face or subface positions and the older-age stand provided almost four times the volume of usable veneer. Standing-tree acoustic wave velocity (AWV) explained a moderate amount of variance in log MOEdyn and Pearson correlation coefficients between the (Metriguard) veneer MOEdyn, log AWV, log MOEdyn and disc basic density were significant, positive and strong, with log AWV explaining most of the observed variance in log stiffness. A moderately strong and positive linear regression existed between log AWV and veneer MOEdyn, supporting the use of log AWV tools for the ranking of stiffness in fibre-grown plantation E. nitens logs. Mechanical strength testing of LVL studs extracted from panels manufactured from the trial's veneer indicated they equalled, and for some tested parameters exceeded, the characteristic design strength values previously published by commercial LVL manufacturers for equivalent size pine products.